Manajemen Bandwidth Pada Jaringan Pemerintah Kota Surabaya Menggunakan Metode Queue Tree - Kriswantoro, M. Cahyo; Ayatullah, Ahmad Hafidh (Applied Information Technology and Computer Science (AICOMS), 2023)
To obtain maximum access speed with limited bandwidth resources, bandwidth requires good regulation to maintain data transfer in a computer network so that data queues do not accumulate due to overloaded access requests in the network, hence the need for Bandwidth Management in a computer network. . Bandwidth Management functions to regulate network bandwidth so that each network user gets equal bandwidth. The Surabaya City Government is an agency that uses computer networks to integrate all existing data. Everything is connected into one unit centered at the Surabaya City Dinkominfo Secretariat Office. In this network there is a Fiber Optic network and an external Fiber Optic network. What will be implemented in this research is on an external fiber optic network. The problem currently being faced is the need for good network management so that the performance of the network being built is in accordance with the devices that have been prepared. The method used is Queue Tree from the MikroTik router. The result of implementing Bandwidth Management is that the network quality using the Queue Tree method is more optimal, because the bandwidth will be divided according to the rules applied to bandwidth management so that clients get bandwidth according to the rules.